Pelatihan Pramusaji Montigo Resort Nongsa Hote Batam - Idham Wibawa; Ilham Fajri; Ilusyana Angkasawati Putri (JURNAL PARIWISATA VOKASI, 2022)
The purpose of this research is to find out the waiter training available at Montigo Resort Nongsa Hotel Batam. Training is something that needs to be done for waiters in restaurants, whether they are new waiters or those who have worked at the restaurant for a long time. The training provides a standard that must be followed by all participants. In training there are several basic things that must be done so that the training runs according to needs and can run effectively and efficiently. The research method used is a quantitative descriptive method which is processed through a questionnaire as a means of collecting data. The population in this study were employees who worked as waiters at the hotel with a total of 18 respondents using a purposive sampling technique. For data collection techniques carried out, namely by conducting observations, interviews, questionnaires, and literature study. Based on the results of the study, it was found that the waiter training was not optimal or it could be said to be lacking because there were still many waiters who had not attended training. Some of these things ultimately resulted in waiter training at Hotel Montigo Resort Nongsa Batam not being able to run properly which in the end was in accordance with the results of observations of guests who stayed where the average guest who stayed was not satisfied with the service provided by the waiter at the hotel. Montigo Resort Nongsa Batam. Keywords: Training, Waiter, Restaurant